Design of a 470 MHz band IoT antenna for a handheld terminal - Sun Nan; Wen Zhiguo; Jiang Fan; Li Yan; Wang Yujing; Zou Jian; Song Ya (Dianzi Jishu Yingyong, 2021)
Many handheld terminal devices require a light and compact receiving and transmitting antenna. FPC antennas are popular among designers because of their light weight and thin thickness. In order to obtain an antenna with suitable size, bandwidth and gain, an FPC soft material is used as an integrated platform, and the transmission line and antenna are used as an integrated design. While maintaining the size of the antenna, the energy coupling of radiating unit is enhanced by adding coupling branches，which effectively improves bandwidth and gain. The integrated design of transmission line and antenna can effectively use the antenna space and improve the port characteristics. Through simulation and actual testing, the antenna bandwidth meets 470 MHz~510 MHz, S11<-10 dB. S11<-12 dB at 490 MHz, the effective gain is 0 dBi.